2017
DOI: 10.1007/s00595-017-1615-6
|View full text |Cite
|
Sign up to set email alerts
|

Development of a new surgical sheet containing both silk fibroin and thermoplastic polyurethane for cardiovascular surgery

Abstract: The SF/TPU sheet had excellent mechanical properties and tissue biocompatibility. These favorable features and possible biodegradability of the SF portion warrant a long-term follow-up study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…At six months post-implantation, the higher SF concentration patch demonstrated progressive remodeling, including significantly higher tissue infiltration, elastogenesis and endothelialization compared with lower SF concentration [21]. In addition to rat studies outstanding results also observed with canine descending aorta replacement with a SF/TPU sheet as a patch [22].…”
Section: Introductionmentioning
confidence: 99%
“…At six months post-implantation, the higher SF concentration patch demonstrated progressive remodeling, including significantly higher tissue infiltration, elastogenesis and endothelialization compared with lower SF concentration [21]. In addition to rat studies outstanding results also observed with canine descending aorta replacement with a SF/TPU sheet as a patch [22].…”
Section: Introductionmentioning
confidence: 99%
“…At 6 months after implantation ( Figure 10 c,d), the thickness of the PU-SF sponge almost disappeared and was further subdivided. Many biomaterials using SF-PU composite materials have been actively studied in the cardiovascular field [ 20 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. However, because the PU used for the composite with SF is generally not biodegradable, it was difficult to use for coating materials in combination with biodegradable SF.…”
Section: Resultsmentioning
confidence: 99%
“…Silk fibroin is one of the major proteins forming the silkworm cocoon, which has shown excellent biocompatibility, biodegradability and mechanical properties, thus silk fibroin is regard as a promising biomaterial in cardiac tissue engineering (33,34). SF has been applied in various forms of biopolymer-based composites as cardiac patches and has demonstrated ideal efficacy (14).…”
Section: Discussionmentioning
confidence: 99%